2021
DOI: 10.3390/cancers13102439
|View full text |Cite
|
Sign up to set email alerts
|

fMRI Retinotopic Mapping in Patients with Brain Tumors and Space-Occupying Brain Lesions in the Area of the Occipital Lobe

Abstract: Functional magnetic resonance imaging (fMRI) is a valuable tool in the clinical routine of neurosurgery when planning surgical interventions and assessing the risk of postoperative functional deficits. Here, we examined how the presence of a brain tumor or lesion in the area of the occipital lobe affects the results of fMRI retinotopic mapping. fMRI data were evaluated on a retrospectively selected sample of 12 patients with occipital brain tumors, 7 patients with brain lesions and 19 control subjects. Analyse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…The high variance of the data may be responsible for the fact that the difference between the two hemispheres was not significant for these two regions. This aligns with published data showing an attenuation of the BOLD signal in the affected hemisphere compared to the contralateral hemisphere for brain tumors in general [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The high variance of the data may be responsible for the fact that the difference between the two hemispheres was not significant for these two regions. This aligns with published data showing an attenuation of the BOLD signal in the affected hemisphere compared to the contralateral hemisphere for brain tumors in general [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, a number of studies have already shown an alteration of the fMRI BOLD (blood oxygenation level dependent) signal in patients with brain tumors in general, in terms of attenuated activation in the affected hemisphere compared to the contralateral one [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. In order to identify intact functional areas, the fMRI BOLD signal uses neurovascular coupling, which may be disturbed especially in the vicinity of higher-grade gliomas due to pathologic neovascularization [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tumors located in the temporal lobes can cause disorders not only in the processing of auditory sensations, but also in speech, verbal memory, recognition of objects and faces, and smells (Yamamoto et al, 2022). Tumors in the occipital lobe can cause blindness, blurred vision, and hallucinations (Hense et al, 2021). Cerebellar tumors affect the ability to coordinate voluntary movements such as balance and blinking whereas brain stem tumors are responsible for disorders of many functions, including basic ones, such as paresis of the limbs, speaking, swallowing, breathing or seeing (Reyes-Botero et al, 2012;Beuriat et al, 2022).…”
Section: Introductionmentioning
confidence: 99%